2017
DOI: 10.1007/s00403-017-1724-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonmelanoma skin cancer and risk of all-cause and cancer-related mortality: a systematic review

Abstract: Some reports suggest a history of nonmelanoma skin cancer (NMSC) may be associated with increased mortality. NMSCs have very low fatality rates, but the high prevalence of NMSC elevates the importance of the possibility of associated subsequent mortality from other causes. The variable methods and findings of existing studies leave the significance of these results uncertain. To provide clarity, we conducted a systematic review to characterize the evidence on the associations of NMSC with: 1) all-cause mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 37 publications
0
39
0
6
Order By: Relevance
“…In a systematic review of this topic, this pattern was consistent across all three studies, and SCC was more strongly associated than BCC with cancer-specific mortality in the lone study to report on this association [53]. Further, the systematic review found that both BCC and SCC were associated with worse survival after a diagnosis with a noncutaneous cancer [53]. The evidence-base on the relationship between a personal history of KC and fatal outcomes is still sparse and therefore awaits more intensive investigation.…”
Section: Keratinocyte Carcinoma and Risk Of Other Cancers And Fatal Omentioning
confidence: 76%
See 1 more Smart Citation
“…In a systematic review of this topic, this pattern was consistent across all three studies, and SCC was more strongly associated than BCC with cancer-specific mortality in the lone study to report on this association [53]. Further, the systematic review found that both BCC and SCC were associated with worse survival after a diagnosis with a noncutaneous cancer [53]. The evidence-base on the relationship between a personal history of KC and fatal outcomes is still sparse and therefore awaits more intensive investigation.…”
Section: Keratinocyte Carcinoma and Risk Of Other Cancers And Fatal Omentioning
confidence: 76%
“…In a cohort study with individual-level data that adjusted for several cancer risk factors, a personal history of SCC was associated with significantly increased risk of all-cause mortality (RR 1.29; 95% CI 1.01–1.54) whereas BCC was not associated with excess mortality [52]. In a systematic review of this topic, this pattern was consistent across all three studies, and SCC was more strongly associated than BCC with cancer-specific mortality in the lone study to report on this association [53]. Further, the systematic review found that both BCC and SCC were associated with worse survival after a diagnosis with a noncutaneous cancer [53].…”
Section: Keratinocyte Carcinoma and Risk Of Other Cancers And Fatal Omentioning
confidence: 95%
“…Eyelid defects can be divided into congenital and acquired and can be due to diverse etiologies, with cutaneous tumors being one of the most prevalent, especially the non-melanoma type [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Non-Melanoma Skin Cancer, abbreviated NMSC, is the most commonly diagnosed disease and is a significant health concern in terms of incidence rate and economic health care costs [1], [2]. According to the American Cancer Society, approximately 3.3 million Americans are diagnosed with NMSC each year [5].…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
“…Non-Melanoma Skin Cancer (NMSC) affects approximately 3.3 million Americans each year and is currently the most commonly diagnosed disease [1], [2], [5]. The common forms of NMSC are Basal Cell Carcinoma (BCC) and Squamous Cell Carcinoma (SCC), with BCC representing about 80% of NMSCs [2], [17] Given the prevalence of NMSC in the human population, understanding the cause and potential treatments is crucial.…”
Section: Introductionmentioning
confidence: 99%